TROPHY SMOOTHIES FOR TEEN BREAKFAST: A BUSINESS MODEL CANVAS APPROACH - Novsa Fakhira; Andina Oktariani; Nimmi Zulbainarni (School of Business, IPB University (SB-IPB), 2020)
Most teenagers in Indonesia ignore breakfast as an important activity and fulfill breakfast with a low quality. Consumption patterns on teenagers today also like practicality and type of food is not monotonous. The aim of this study is to provide solutions to overcome breakfast for teenagers who like practicality with smoothies. The solution offered by a smoothie’s business model is right to be used as a business opportunity in fulfilling the need for breakfast. This study uses a customer discovery approach with the Business Canvas model. The results of this study found that 100% of teenagers claimed to be interested in buying smoothies for breakfast with the value proposition of smoothies offered, which is a practical breakfast made from tropical fruits and vegetables mixed with milk and without artificial sweeteners. With positive responses from teenagers, the sale of smoothies can be done through collaboration with schools and colleges for the availability of smoothies for students and college students. The financial results of the smoothie’s business show that this business is profitable. Keywords: breakfast, business model canvas, customer discovery, smoothies